2009
DOI: 10.1088/0953-8984/21/22/224025
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam sputtered nanostructured semiconductor surfaces as templates for nanomagnet arrays

Abstract: The ongoing tendency for increasing the storage densities in magnetic recording techniques requires a search for efficient routes to fabricate and characterize nanomagnet arrays on solid supports. Spontaneous pattern formation in semiconductor heteroepitaxy or under ion erosion of semiconductor surfaces yields nanostructured substrates that can serve as templates for subsequent deposition of magnetic material. The nanostructured morphology of the template can easily be replicated into the magnetic coating by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Shadow deposition at moderate angles between 20 and 45° allows the formation of nanomagnet sizes below 20 nm and storage densities of at least 0.2 Tbit in -2 . [ 165 ]. Alternatively, deposition of homogeneous thin films, covered by an overlayer susceptible to pattern formation and subsequent ion erosion of this top-layer, leading to a structured surface topography with local variations in the effective sputter yield, will lead to ordered arrays of magnetic nanoparticles [ 166 , 167 ].…”
Section: Selected Applicationsmentioning
confidence: 99%
“…Shadow deposition at moderate angles between 20 and 45° allows the formation of nanomagnet sizes below 20 nm and storage densities of at least 0.2 Tbit in -2 . [ 165 ]. Alternatively, deposition of homogeneous thin films, covered by an overlayer susceptible to pattern formation and subsequent ion erosion of this top-layer, leading to a structured surface topography with local variations in the effective sputter yield, will lead to ordered arrays of magnetic nanoparticles [ 166 , 167 ].…”
Section: Selected Applicationsmentioning
confidence: 99%
“…It was shown that the morphology of the nanorippled substrates modifies the magnetic properties of ultrathin single-crystalline [19] and poly-crystalline [20,21,22] metal films. In a similar manner, arrays of close-packed nanomagnets could recently be obtained by shadow deposition on hexagonally ordered dot patterns [23]. Moreover, the self-organized alignment of physical-vapor deposited metal nanoparticles on nanorippled substrates was recently observed, leading to large arrays of nanoparticle chains exhibiting polarization-dependent plasmon absorption [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…With the same technique, also arrays of metallic nanowires could be produced [26,27,28]. Most of these applications crucially depend on certain properties of the template patterns such as a high degree of order in the case of storage media [17,23] or a well defined ripple wavelength that fits to the growth conditions of the nanoparticles [24]. A precise control of the pattern properties in turn requires detailed knowledge of the pattern formation process and the contributing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The domain sizes are in the range of 100 nm corresponding to the grain size in the as-deformed state [12], indicating single-domain behavior. To qualitatively characterize the morphology and magnetic domain sizes for each annealing temperature, we employ the following procedure which has been introduced for a comprehensive surface roughness characterization [26,27] but can also be applied to the MFM signal [28]. This procedure considers so-called auto-correlation and height-height correlation functions [26].…”
Section: Magnetic Force Microscopymentioning
confidence: 99%